2015
DOI: 10.5114/pm.2015.54343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selected factors on the osseointegration of dental implants

Abstract: IntroductionOsseointegration of dental implants with the maxillary and/or mandibular bone is the basis for implant prosthetic treatment. The aim of the study was to assess the influence of the patients’ gender, age, and in the case of women, their menopausal status (before menopause/after menopause/during hormone replacement therapy) on the osseointegration of dental implants.Material and methodsThe study evaluated the bone loss after implant loading and the success rate of the procedure in 71 women and 30 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 9 publications
(11 reference statements)
1
21
0
2
Order By: Relevance
“…In this study, no difference was noted between implants placed in patients on BPs and those placed in patients without BP intake, 4-6 months after installation at second-stage surgery, with both groups exhibiting peri-implant marginal bone levels that are considered as normal (0.87 vs. 0.92 mm, respectively) (Laurell & Lundgren, 2011). In the two studies reporting on marginal bone levels around implants placed in HRT vs. control patients, significantly more bone loss both during the osseointegration phase (Koszuta et al, 2015) and on the long term (de Souza et al, 2013) was observed in the HRT group; however, the studies did not provide precise values in mm. Additionally, in 90% of the implants, peri-implant marginal bone loss was <1.5 mm, and the small number of implants (i.e., 2.5%) exhibiting a peri-implant marginal bone loss >3 mm was not specifically associated with BP intake.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this study, no difference was noted between implants placed in patients on BPs and those placed in patients without BP intake, 4-6 months after installation at second-stage surgery, with both groups exhibiting peri-implant marginal bone levels that are considered as normal (0.87 vs. 0.92 mm, respectively) (Laurell & Lundgren, 2011). In the two studies reporting on marginal bone levels around implants placed in HRT vs. control patients, significantly more bone loss both during the osseointegration phase (Koszuta et al, 2015) and on the long term (de Souza et al, 2013) was observed in the HRT group; however, the studies did not provide precise values in mm. Additionally, in 90% of the implants, peri-implant marginal bone loss was <1.5 mm, and the small number of implants (i.e., 2.5%) exhibiting a peri-implant marginal bone loss >3 mm was not specifically associated with BP intake.…”
Section: Discussionmentioning
confidence: 97%
“…All studies, but one prospective study (Koszuta et al, 2015), were retrospectively based on medical/dental records. All studies, but one prospective study (Koszuta et al, 2015), were retrospectively based on medical/dental records.…”
Section: Studies On Hrt Intake (N = 7)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has to be noted that a greater number of female patients and smokers have been found in one of the two groups in four [19,21,23,26] and three [19,23,25] studies, respectively, which could be considered a possible source of confounding factors. For the female patients, a recent study by Koszuta et al [28] reported that, while gender itself does not affect the amount of implant failures, the patients receiving hormonal therapy are at a greater risk of losing their implants. As for smokers, recent studies [29,30] have pointed that the habit of smoking has a harmful effect upon the surrounding bone, thus compromising the osseointegration.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our findings point out that standard implants placed in regenerated bone have a higher bone loss over time when compared with short implants; however, this evidence is only corroborated by two available RCT. Several variables such as surgical technique [41,42], implant design and connection [43], prosthetic considerations [28] or patient-centred variables [44] have to be considered aswell.…”
Section: Discussionmentioning
confidence: 99%